ANALISIS PERMINTAAN DAGING AYAM RAS DI KABUPATEN KUDUS - Firda Nur Fitriana; Joko Sutrisno; Susi Wuri Ani (Universitas Sebelas Maret, 2019)
The research has purpose, such as to examine the factors influencing the demand of broiler chicken’s meat in Kudus Regency and to analyze the demand forecase of broiler chicken’s meat in Kudus Regency. The sampling of research location is done purposively. The type of data used are secondary data from January 2016 until December 2017. The method of analysis used to estimate the demand function is linier regression method with classical assumptions. The result of regression analysis showed that independent variables have a significant influence on the dependent variable with R2 adjusted value of 0,953. Partially, broiler chicken’s meat cost, chicken’s eggs cost, milkfish cost, cooking oil cost, and income per capita, each influencing the demand of broiler chicken’s meat in Kudus Regency. Elasticity coefficient of broiler chicken’s meat cost (-0,482), is called inelastic. Broiler chicken’s meat is substitute with milkfish (0,288). Broiler chicken’s meat is complementary with chicken’s eggs (-0,341) and cooking oil (-0,425). Broiler chicken’s meat is a staple goods with a positive elasticity value (0,684). Researchers suggest to broiler breeders to increase their production capacity to meet the needs of broiler chicken in Kudus Regency.